Multimodal Analysis in Covid-19 Advertisement of Indonesia and Arabic Version - Nazwa Mustika; T. Thyrhaya Zein; Rahimah Rahimah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The COVID-19 advertisement made by the Indonesian and Arab governments on the official website of the Ministry of Health's online media is a Public Service Advertisement (ILM) which aims to educate the public in dealing with this pandemic. This research will discuss the verbal and visual texts contained in the Indonesian version of the COVID-19 advertisement using a functional systemic linguistic approach (Halliday, 1985) and (Kress & Leeuwen, 2006) multimodal analysis model. The purpose of this research is to see how to construct and interpret meaning. discourse with words and images of COVID-19 in Indonesia and Arabic and how the images and words in the discourse are linked how the images and words in the discourse are linked. The method used is a descriptive qualitative method. The results obtained in this study is an ideational function consisting of material processes, mental processes, relational processes, behavioral processes, verbal processes and physical processes.